O crepúsculo em Santiago: a jornada do peregrino rumo à religiosidade e a descoberta analítica - Guimarães, Waldinei Comercio de Souza (2008)
The rediscovery of pilgrimage to Santiago de Compostela observed during the last couple of decades of the twenty century inspire the investigation upon the causes and to follow the events that come in the lives of those who are determined to accomplish the journey in the course of Post Modern age. This investigation takes place effectively when we define the field of knowledge that is able to help us to understand the phenomena; according to this statement we started with Anthropology, which help us to illuminate the pilgrimage considering the social movements around the rites, the religion, spirituality and the search of meaning present in the human history until these days. The meanings of each rite, symbol, and gesture, have suffered modifications along the history, however they preserve their essence. The pursuit of the modern pilgrim s vision concerning the transformations that happen along the Caminho , lead us to do research among some of the pilgrims of Santiago and check the hypotheses proposed in this project. In this sense, we observed that the experience is capable of reconnecting the person to his or her religiosity and the transcendence enabled through the rite. Finally, we analyze the Hero s Journey of Joseph Campbell and according to the Jung s thoughts, establishing relations between the myth structure and the archetypical expressions. Beginning with an analysis of the data obtained in this research, we found elements that reveal the capability of transformation generated by the rite of pilgrimage to Santiago, a fundamental component in the development process of the self